Leveraging Supply Chain Leadership for Dynamic Capabilities and Organisational Resilience - Mokhtar, Ahmad Rais; Anindita, Muhammad Surya; Suhaimi, Zakiah Syamra’ (Advances in Social Sciences Research Journal, 2023)
Organisational resilience has been identified as one of the critical factors in developing sustainable supply chains. To date, extant research discusses the role of dynamic capabilities in enhancing organisational resilience, particularly in developing and reconfiguring internal and external resources to address the changing business environment. Unfortunately, little attention has been paid to exploring the impact of buying firms’ leadership (or supply chain leadership) on the existing relationships between dynamic capabilities and organisational resilience. As a firm’s performance has a significant impact on its entire supply network (in both upstream and downstream orientations), the responsibility to improve organisational resilience could be extended to the buying or focal firms, particularly during unprecedented times such as the pandemic. This study aims to propose a conceptual framework for examining the impact of dynamic capabilities and organisational resilience. In general, this study suggests that dynamic capabilities (adaptive, absorptive, and innovative capabilities) have a significant impact on organisational resilience. Furthermore, this study proposes that supply chain leadership moderates the relationship between dynamic capabilities (adaptive, absorptive, and innovative capabilities) and organisational resilience. It is expected that this study will facilitate discussions on the need to deepen the comprehension of supply chain leadership and its influence on dynamic capabilities and organisational resilience. The study contributes to the existing literature by addressing the gaps between supply chain leadership, dynamic capabilities, and organisational resilience domains.